Creutzfeldt–Jakob disease: A case report - Fahad Rasool Butt, HBSc; Thanansayan Dhivagaran, HBSc; Syed Naqvi, MD, FRCPC, DABR (Radiology Case Reports)
Creutzfeldt–Jakob Disease (CJD) is a rare, fatal neurodegenerative disorder that is caused by prion proteins. Patients often present with rapidly progressive dementia, ataxia, myoclonus, memory impairment, visual problems, and changes in personality. In this case report, we aimed to address the course of a 62 year old female who presented with progressive decline in cognitive function and died within 6 months of presentation. The patient underwent cerebrospinal fluid testing, MRI brain, and electroencephalography during her stay in the hospital. Ultimately, an autopsy was performed, which demonstrated spongiform changes, neuronal loss, and astrogliosis, consistent with CJD.